The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae) - Nel, Andre; Perreau, Ziann; Doitteau, Gaelle (Zootaxa, 2016)
We describe and illustrate from the earliest Eocene amber of France the oldest representative of the rhagionid modern genus Symphoromyia, under the name of S. eocenica sp. nov. Its mouthpart structure shows that it was hematophagous as is the modern representatives of the genus, demonstrating a remarkable morphological stability for 53 Myr.